PENGARUH PENGALAMAN, KEPERCAYAAN, CITRA TERHADAP LOYALITAS MEREK DAN DAMPAKNYA TERHADAP SIKAP KONSUMEN PADA PERLUASAN MEREK OBAT FLU DAN BATUK - Handoyo, Handono (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
The pharmaceutical sector in Indonesia has grown by 12.5% per year, as prescriptiondrugs, Over the Counter (OTC) medicines and dietary supplements (nutrition and vitamins) allexperience increased sales. Bodrex is one type of over-the-counter medication to overcome theheadache that has been well known and believed for more than 45 years by the people in Indonesiaand then innovate manufacturers to expand the brand by launching Bodrex Flu and Cough.IMS datamarket shared Flu and Cough drug of Bodrex sales decline every year ie in 2013 amounted to 1.10%,in 2014 amounted 0.89% and in 2014 amounted to 0.84%. The purpose of this research was todetermine the effect of marketing mix composed of product, price, promotion and place of the brandloyalty so that the impact on consumer brand extension attitude. Questionnaire with closed questionsare used as design research instrument, and as many as 200 respondents were sampled in theresearch. Methods of SEM (Structural Equation Modeling) is used as a technique of data analysis,SPSS 16 and Lisrel 8.7 for windows was used to analysis the data obtained after the research. Theresearch shows that the experience, trust and image simultaneously influence the brand loyalty sothat the impact on consumer brand extension flu and cough drug eligible Goodness of fit. Partiallybrand experience significantly influence brand loyalty with t values 2.12. Partially Brand Trustaffects loyalty because it has a t value of 0.97. Partially Brand Image significant effect on purchasingdecision because have value 2,93.Secara Partial Loyalitas significant influence to ConsumerAttitude on Brand Extension because have value 11,11.